(untitled) - Mead, Richelle (New York, NY, 2014)
In the aftermath of an event that ripped their world apart, Sydney and Adrian struggle to pick up the pieces and find their way back to each other. But first, they have to survive.
Keywords: Juvenile fiction; Secrets; Fiction; Vampires; Juvenile fiction; Fiction; Vampires; Fiction; Survival; Fiction; Secrets; Survival; Love; Juvenile fiction